Pd nanoparticle and molecular Pd2+ leaching pathways for a strongly acid versus strongly basic resin supported Pd nanoparticle catalyst in Suzuki coupling - Van Vaerenbergh, Beau; Lauwaert, Jeroen; Thybaut, Joris W.; Vermeir, Pieter; De Clercq, Jeriffa (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •The leaching behaviour and mechanisms are elucidated via combined data analysis.•A homogeneous-heterogeneous catalytic system prevails for both NP catalysts.•The leaching pathway critically depends on the resin functionality.•Phenylpalladium(II)hydroxide complexes are proposed as the leached Pd2+ species. The Pd leaching behaviour of a strongly acid (Lewatit K2629) versus strongly basic (Lewatit MP500 OH) ion exchange resin supported Pd nanoparticle (Pd-NP) catalyst is elucidated in the Suzuki reaction between iodobenzene and phenylboronic acid with K2CO3 as base in 1:1 (v/v) DMF/H2O at 40 °C. Reaction and leaching kinetic analyses combined with hot filtration tests indicated heterogeneous-homogeneous catalysis for both Pd-NP catalysts. More particularly, leaching experiments showed that for Pd-NP Lewatit K2629, Pd-NP as well as molecular Pd2+ leaching (as phenylpalladium(II)hydroxide complexes) occurred due to, respectively, the disturbance of the electrostatic NP stabilization by dissociated K2CO3 and reaction with iodobenzene and hydroxide. For Pd-NP Lewatit MP500 OH, however, molecular Pd2+ leaching induced by iodobenzene, dominates. Hence, the resin functionality determines the contribution of each leaching pathway. Furthermore, at high conversions, Pd re-deposition occurred due to the decreased amount of leaching inducing reagents causing enlarged NPs in the resin which leached less in subsequent runs.